1995
DOI: 10.4049/jimmunol.155.10.5046
|View full text |Cite
|
Sign up to set email alerts
|

CD8highCD57+ T lymphocytes in normal, healthy individuals are oligoclonal and respond to human cytomegalovirus.

Abstract: CD8+CD57+ lymphocytes from normal peripheral blood are divided into T cells expressing high levels of CD8 and NK cells expressing low levels of surface CD8. Increased numbers of CD8highCD57+ T cells correlate with previous exposure to human cytomegalovirus (HCMV) infection, but no virus-specific function or function for CD8highCD57+ cells has been recorded. We have studied the TCR repertoire and responses of the CD8highCD57+ population induced by virus-infected fibroblasts in healthy individuals. Using three-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Percentages of CD4+ and CD8+ T cells with the CD28+CD57− phenotype were significantly loweramong CMV-seropositive as compared to -seronegative subjects, while percentages of CD4+ and CD8+ T cells with the CD28−CD57+ phenotype were significantly higher among seropositive as compared to seronegative subjects (Table 2). These results are in agreement with those reported by others [12,34,36,39,41]. Our study further demonstrated marginal associations of CD8+CD28−CD57+ T cells with a pathological diagnosis of Alzheimer disease (by NIA-Reagan criteria) and CD4+CD28−CD57+ T cells with accumulation of Aβ (Table 3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Percentages of CD4+ and CD8+ T cells with the CD28+CD57− phenotype were significantly loweramong CMV-seropositive as compared to -seronegative subjects, while percentages of CD4+ and CD8+ T cells with the CD28−CD57+ phenotype were significantly higher among seropositive as compared to seronegative subjects (Table 2). These results are in agreement with those reported by others [12,34,36,39,41]. Our study further demonstrated marginal associations of CD8+CD28−CD57+ T cells with a pathological diagnosis of Alzheimer disease (by NIA-Reagan criteria) and CD4+CD28−CD57+ T cells with accumulation of Aβ (Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…Cryopreserved PBMCs from CMV-seropositive subjects were analyzed by flow cytometry to determine the percentages of CMV-specific CD4+ and CD8+ T cells by intracellular expression of IFN-γ and TNF-α in response to the CMV-specific antigen, pp65. Cells positive for both cytokines were detected in CD8+ and CD4+ T-cell subsets in all samples; however, mean percentages (Table 2) were lower than reported elsewhere [7,[33][34][35][36]. One possible reason for the lower detectable response rate was the use of only a single CMV-specific antigen in the assay.…”
Section: Cmv-specific T Cellsmentioning
confidence: 60%